2018
DOI: 10.1186/s12859-018-2217-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating methods of inferring gene regulatory networks highlights their lack of performance for single cell gene expression data

Abstract: BackgroundA fundamental fact in biology states that genes do not operate in isolation, and yet, methods that infer regulatory networks for single cell gene expression data have been slow to emerge. With single cell sequencing methods now becoming accessible, general network inference algorithms that were initially developed for data collected from bulk samples may not be suitable for single cells. Meanwhile, although methods that are specific for single cell data are now emerging, whether they have improved pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
240
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(248 citation statements)
references
References 45 publications
7
240
0
1
Order By: Relevance
“…Uncovering these regulatory interactions is the goal of gene regulatory network (GRN) inference methods. Gene regulatory network inference is performed based on measurements of gene co-expression such as correlation, mutual information, or via regression models (Chen & Mar, 2018). If two genes show a co-expression signal even when all other genes are taken into account as potential confounders, these genes are said to have a causal regulatory relationship.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncovering these regulatory interactions is the goal of gene regulatory network (GRN) inference methods. Gene regulatory network inference is performed based on measurements of gene co-expression such as correlation, mutual information, or via regression models (Chen & Mar, 2018). If two genes show a co-expression signal even when all other genes are taken into account as potential confounders, these genes are said to have a causal regulatory relationship.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…While there exist GRN inference methods that were specifically developed for scRNA‐seq data (SCONE: Matsumoto et al , ; PIDC: Chan et al , ; SCENIC: Aibar et al , ), a recent comparison has shown both bulk and single‐cell methods to perform poorly on these data (Chen & Mar, ). GRN inference methods may still offer valuable insights to identify causal regulators of biological processes, yet we recommend that these methods be used with care.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we considered how to simulate these networks to create in silico single-cell gene expression datasets. Several recent studies on GRN inference from such data [7,9,10,18,27] have used GeneNetWeaver [23], a method originally developed for generating time courses of bulk-RNA datasets from a given GRN. Accordingly, we simulated the six synthetic networks using GeneNetWeaver via the procedure outlined in Chan et al [7] (see Supplementary Section S1 for details).…”
Section: Datasets From Synthetic Networkmentioning
confidence: 99%
“…We start this section by giving an overview of GeneNetWeaver [23], a popular method for simulating bulk gene expression datasets. It is being used increasingly for simulating single cell transcriptional data as well [7,9,10,18,27]. Next, we describe the BoolODE framework that we have developed and highlight its differences with GeneNetWeaver.…”
Section: S1 Boolode: Converting Boolean Models To Ordinary Differentimentioning
confidence: 99%
See 1 more Smart Citation